Cover Feature: Photophysics of Up‐Conversion Nanoparticles: Radical Photopolymerization of Multifunctional Methacrylates Comprising Blue‐ and UV‐Sensitive Photoinitiators (ChemPhotoChem 11/2019). Issue 11 (4th November 2019) - Oprych, Dennis; Schmitz, Christian; Ley, Christian; Allonas, Xavier; Ermilov, Eugeny; Erdmann, Rainer; Strehmel, Bernd
Abstract : The Cover Feature illustrates the application of lanthanide‐doped upconversion nanoparticles in which several photons are involved to emit UV light generated upon near‐IR irradiation. This emission was studied by time‐correlated single photon counting (TCSPC) and applied to cure coatings via photopolymerization with a high‐power line‐shaped laser. More information can be found in the Article by D. Oprych et al. on page 1119 in Issue 11, 2019 (DOI: 10.1002/cptc.201900196 ).